Impact of seawater warming and nutrient deprivation on the physiology and energy metabolism of corals - Pupier, Chloé A.; Grover, Renaud; Rottier, Cécile; Ferrier-Pagès, Christine (Frontiers in Marine Science, 2024)
Seawater temperature and the availability of dissolved inorganic nutrients (DINut) have a major influence on the stability of the symbiosis between corals and Symbiodiniaceae. In particular, seawater warming or DINut depletion can lead to coral bleaching, the loss of Symbiodiniaceae from coral tissue. However, the combined effects of heat stress and DINut deficiency on the coral energy metabolism are still understudied. Here, we investigated the physiological and energetic responses of the octocoral Heteroxenia fuscescens and the hexacoral Stylophora pistillata exposed to two levels of inorganic nutrients in seawater (control, depleted) and two temperatures, 25°C (control) and 30°C (high temperature), in a crossed factorial design. Our results show that thermal and DINut stress both decreased the photosynthesis to respiration ratio of the two species and induced bleaching in H. fuscescens. While nutrient deprivation had little effect on the corals’ energy metabolism, heat stress led to higher concentrations of macromolecules such as carbohydrates and lipids, as well as anaerobic metabolism, and decreased ATP production in H. fuscescens. Given that the intensity and frequency of marine heatwaves will significantly increase in the future, there is an urgent need to investigate the processes by which corals can overcome starvation.